Christianity and market regulation : an introduction / edited by Daniel A. Crane, University of Michigan, Ann Arbor; Samuel Gregg, Acton Institute. - Crane, Daniel A.; Gregg, Samuel, 1969- (Law and Christianity., 2021)
Historically, the Christian tradition has played an influential role in Western economic thought concerning the regulation of markets, but, with the fracturing of the Christian tradition following the Reformation, the decline of Christian influence in academia, and the increasing specialization of economic analysis, that influence has become increasingly opaque. This volume brings together an interdisciplinary team of prominent academic experts on market regulation from four different continents and various faith traditions to reconsider the impact of Christianity on market regulation. Drawing on law, economics, history, theology, philosophy, and political theory, the authors consider both general questions of market regulation and particular regulatory fields such as bankruptcy, corporate law, and antitrust from a Christian perspective.